The use of low‐titer group O whole blood is independently associated with improved survival compared to component therapy in adults with severe traumatic hemorrhage. Issue Volume 60:Issue S3(2020) (1st June 2020) - Shea, Susan M.; Staudt, Amanda M.; Thomas, Kimberly A.; Schuerer, Douglas; Mielke, James E.; Folkerts, Danielle; Lowder, Ethan; Martin, Callista; Bochicchio, Grant V.; Spinella, Philip C.
Abstract : BACKGROUND: There is a resurgence in the use of low‐titer group O whole blood (LTOWB) for hemorrhagic shock. We hypothesized the use of LTOWB compared to component therapy (CT) would be independently associated with improved 24‐hour mortality. STUDY DESIGN AND METHODS: In this prospective observational study, trauma patients 18 years of age or older with massive transfusion protocol activations were included from August 17, 2018, to May 14, 2019. The primary outcome was 24‐hour mortality. Secondary outcomes included 72‐hour blood product totals, multiple organ dysfunction scores (MODS), and 28‐day mortality. Multivariable logistic regression (MVLR) and Cox regression were performed to determine independent associations. RESULTS: There were no clinically meaningful differences in measures of injury severity between study groups (CT, n = 42; LTOWB, n = 44). There was no difference in MODS between study groups. The unadjusted mortality was not statistically different between the study groups (9/42 [21%] for CT vs. 7/44 [16%] for LTOWB; p = 0.518). In the MVLR model, LTOWB increased the odds of 24‐hour survival by 23% (odds ratio 0.81, 95% confidence interval 0.69‐0.96; p = 0.017). Adjusted survival curve analysis indicated improved survival at both 24 hours and 28 days for LTOWB patients (p < 0.001). Further stratification showed an association between LTOWB use and survival when maximum clot firmness (MCF) was 60 mm or less (p = 0.009). CONCLUSIONS: The use of LTOWB is independently associated with improved 24‐hour and 28‐day survival, and does not increase organ dysfunction at 72 hours. Use of LTOWB most impacted survival of patients with reduced clot firmness (MCF ≤60 mm). Collectively, these data support the clinical use and continued study of LTOWB for hemostatic resuscitation.